Ethosomes serve as a non-invasive drug delivery system capable of penetrating the skin, merging with cell membrane lipids, and releasing pharmaceuticals - Bhavana Radhika Hemanth (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
The skin is one of the largest and most accessible organs in the human body, and its application as a pathway for drug delivery presents several advantages compared to conventional drug delivery systems. These benefits encompass reduced variability in plasma medication concentrations, prevention of gastrointestinal complications and first-pass metabolism, along with enhanced patient adherence. Transdermal drug delivery systems (TDDS) are characterised as self-contained, discrete dosage forms that, upon application to undamaged skin, administer medications at a controlled rate to the systemic circulation. Ethosomes are innovative lipid carriers consisting of ethanol, phospholipids, and water. These ethosomes are engineered as a non-invasive drug delivery method capable of penetrating the skin, merging with cell membrane lipids, and releasing the drug. Ethosomes can be prepared by either thermal or non-thermal processes. Evaluation criteria for ethosomes encompass dimensions, morphology, drug concentration, and zeta potential. Ethosomes have been effectively assessed for the administration of multiple pharmaceuticals, including cyclosporine, insulin, and salbutamol. Ethosomes possess significant potential as a crucial medication delivery mechanism in the future